2020
DOI: 10.1051/e3sconf/202021017007
|View full text |Cite
|
Sign up to set email alerts
|

Rational psychotherapy of neuroses: dynamic changes in psychological response of men and women

Abstract: The paper presents the results of a study of dynamic changes in the severity of depression, it’s somatic manifestations, basic beliefs and dysfunctional attitudes in the course of treatment which included rational psychotherapy. The study sample consisted of 48 men and women with different forms of prediagnosed neurotic disorder aged 25-44 years (M = 32.6, SD = 5.3 (43.7% men)). Methods: Beck Depression Inventory (BDI, N.V. Tarabrina, 2001), Beck Anxiety Inventory (BAI, N.V. Tarabrina, 2001), Janoff-Bulman The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been proved that the art-therapeutic process contributes to the prevention of neurosis-like personality states, the elaboration and outpouring of negative emotions, internal contradictions, helps to increase the level of awareness of one's feelings, take control of them which provides relaxation, relieving of mental tension, increasing of self-esteem [19], helps with interpreting displaced experiences, accepting one's feelings and experiences [16]. Moreover, art therapy is effective in working with people experiencing crisis conditions, in correcting the consequences of psychotraumatic stress, therapy of mental disorders [20,21], in the medical and psychosocial rehabilitation of mental patients [22,23]. All these problems intensify the personality alcoholization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that the art-therapeutic process contributes to the prevention of neurosis-like personality states, the elaboration and outpouring of negative emotions, internal contradictions, helps to increase the level of awareness of one's feelings, take control of them which provides relaxation, relieving of mental tension, increasing of self-esteem [19], helps with interpreting displaced experiences, accepting one's feelings and experiences [16]. Moreover, art therapy is effective in working with people experiencing crisis conditions, in correcting the consequences of psychotraumatic stress, therapy of mental disorders [20,21], in the medical and psychosocial rehabilitation of mental patients [22,23]. All these problems intensify the personality alcoholization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the effectiveness of therapy is often determined by personality characteristics [15,16]. In the development of chemical addiction, the peculiarities of its course and the prognosis of the results of rehabilitation, the personality characteristics of addicts also matter.…”
Section: Introductionmentioning
confidence: 99%
“…believes that the necessary personal qualities of a medical worker are: empathy, authority, sincerity, dedication, humanity, decency, personal maturity, restraint, accuracy, high self-discipline, optimism, mindfulness, high emotional stability and sensorimotor development (correct, dexterous, harmonious movements). Conscientious medical worker contraindicated neglect, blackness, cynicism, indifference, temper, promiscuity, negligence, arrogance, acrimony [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%